Exploring External Influences on Cryptocurrency Prices: Using A Multi-Analytical Approach - Daruwala, Zaheda (International Journal of Economics and Financial Issues, 2025)
Cryptocurrencies have experienced exponential growth within the last decade, with market capitalization hovering above the one-trillion-dollar mark since 2022. One area of concern for current and potential crypto users and investors is their unprecedented price volatility. As cryptos become interlinked with the regulated financial system, questions emerge regarding the possibility of linkages of their prices to the external environments. Financial and macroeconomic factors of inflation, economic growth, interest rates, currency exchange rates, equity market returns, corporate bond yields, gold and oil prices are examined against the cryptocurrency returns. This study encompasses a multi-analytical approach, firstly with the empirical tests of Spearman’s correlational analysis to discover the most pertinent relationships, followed by the PCA analysis to reduce redundancy. The predictive regression model of the Granger Causality test, a vector autoregression (VAR) time series forecasting method, is applied to examine whether the highly effective factors Granger cause the crypto price movements. The Machine Learning Random Forest Regression is also applied where a nuanced understanding of the external factors affecting cryptos prices is gained. The findings of this study pertain to more recent times when the pandemic crisis has subsided and stable economies are in place. The results examined four major cryptos of Bitcoin, Binance Coin, Ripple and Tether, where most behaviours suggest that users and investors are willing to take on riskier assets during periods of economic growth, a strong equity market complements crypto demands and gold and oil are good substitutes for cryptos. Tether, a stablecoin, was the least impacted by external factors and behaved similarly to a fiat currency. This investigation into external factors will empower cryptocurrency users and investors with valuable insights into the crypto price mechanisms, enabling them to refine their investing and portfolio diversification strategies.